Determinants of tax compliance behaviour among individual taxpayers in Malaysia - Lim, Yi Hang; Lim, Wei Sern; Low, Wei Xuan (2024)
This study explores the determinants of tax compliance behaviour among individual taxpayers in Malaysia, through the lenses of the Theory of Planned Behaviour (TPB) and the Slippery Slope Framework (SSF). The research examines the impact of four key variables: tax knowledge, tax morale, trust in government, and the power of authorities on tax compliance behaviour. A detailed literature review provides context for the theoretical and empirical relationships among these variables. The research framework is tested using multiple linear regression analysis. The findings reveal that tax morale, trust in government, and the power of authorities have a significant positive impact on tax compliance behaviour. Specifically, higher tax morale and greater trust in government are associated with increased compliance, while the perceived power of authorities also contributes positively to compliance levels. In contrast, tax knowledge is found to be an insignificant predictor of tax compliance behaviour in this context. These results suggest that fostering a positive tax morale, building trust in governmental institutions, and enhancing the perceived authority of tax authorities are crucial for improving tax compliance. The study highlights the limited role of tax knowledge in influencing compliance behaviour and provides actionable insights for policymakers seeking to enhance tax compliance strategies. The findings contribute to a deeper understanding of tax compliance behaviour in Malaysia, considering the country’s unique socio-economic and cultural landscape.